Exploiting commodity parallel hardware for computer graphics applications and architectures - O'Conor, Keith (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2007)
The processing power available in today's commodity parallel hardw are has enabled realism and detail in graphics that has never before been possible. With the advent of the progrannnable Graphics Processor Unit (GPU), the full potential of parallel architectures to accelerate graphics algorithms has become apparent. This parallelism is becoming more ubiquitous in other processors, and research that exploits this parallelism is ongoing.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin